PENERAPAN DAN FUNGSI MANAJEMEN RISIKO FLUKTUASI HARGA BATU BARA BERDASARKAN ISO 31000 (Studi Kasus pada Perusahaan Distributor Alat Berat PT X) - Aqmarina Awalianti; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2014)
This paper examines the implementation and the advantage of risk management based on ISO 31000. This research focuses on the implementation of risk management to manage the coal price volatility risk in heavy equipment distributor called PT X. The purpose of this research is to conceive the commitment of PT X in implementing risk management, analyze how PT X manages the coal price volatility risk, and conceive the advantage after implementing risk management. A triangulation approach was adopted to get data collection and analysis for the study. Risk management unit of PT X and PT Y, as the parent company of PT X, had been chosen as the sample of this qualitative research. From the result of interview process with several informants and company’s documents, it is found that there is suitability of the risk management implementation in PT X with ISO 31000. PT X started the implementation of risk management by having strong commitment from the company, such as by having strong commitment and mandate from the top management, company’s risk management culture, company policy related to risk management, and company’s risk management organization structure. PT X manages the coal price volatility risk by implementing a series of process of identifying risk, analyzing risk, risk control, risk treatment, monitoring, and review. PT X gains several advantages of implementing risk management, such as obtaining assurance of the strategy implementation, providing information for decision-making process and strategy establishment, and embedding the risk awareness among managerial levels.